Organizational Culture and Employee Transfers Influence on Employee Performance with Work Motivation as Moderator Variable - Kunto Wibisono; Siti Kusandhitasari Jayaningrum; Yuyun Wahyuni; Carmelita Amaya Dacruz (Cita Konsultindo Research Center, 2024)
This research aims to examine the influence of the variables Organizational Culture and Employee Transfers on Employee Performance with Work Motivation as a moderator variable at PT Angkasa Pura I (Persero). The case study was conducted on employees of PT. Angkasa Pura I (Persero) at El Tari Kupang Airport by distributing questionnaires directly. The sample for this research consisted of 200 respondents. The analysis method used is a multilevel test (Hierarchical regression) using the statistic program for social science version 24. Based on the results of data analysis, it shows that H1: Organizational Culture is proven to have a significant influence on Employee Performance, H2: Employee Transfers are proven to have a significant influence on Employee Performance, H3: Organizational Culture is proven to have a significant influence on Employee Performance with Work Motivation as a moderator variable, and H4: Mutations Employees are proven to have a significant influence on employee performance with work motivation as a moderator variable at PT Angkasa Pura I (Persero). Keywords: organizational culture, employee transfers, employee performance, work motivation